Comparison of the tuberculin test, histopathological examination, and bacterial culture for the diagnosis of tuberculosis (Mycobacterium bovis) in buffaloes (Bubalus bubalis) in Brazil - Albernaz, Tatiane Teles; Oliveira, Carlos Magno Chaves; da Silva Lima, Danillo Henrique; da Silva e Silva, Natália; Cardoso, Douglas Pinheiro; Lopes, Cinthia Távora Albuquerque; de Farias Brito, Marilene; da Silva, Jenevaldo Barbosa [UNESP]; Salvarani, Felipe Masiero; Leite, Rômulo Cerqueira; Barbosa, José Diomedes (Springer Nature, 2015)
Tuberculosis is a disease with a great zoonotic potential. It is considered a major obstacle to cattle production and is responsible for severe losses in several production systems. A comparative cervical test (CCT) was performed in 1140 buffaloes from different mesoregions of the state of Pará, Brazil, with the aim of comparing the sensitivity and specificity of CCT with histopathological examination and bacterial culture. Of the animals tested using CCT, 4.65 % (53/1140) were positive, 2.98 % (34/1140) were inconclusive, and 92.36 % (1053/1140) were negative. Among the 168 sacrificed animals, 33 were positive, 18 were inconclusive, and 117 were negative by CCT, and samples from the sacrificed animals were collected for histopathological examination and bacterial culture. A qualitative evaluation of the tuberculin test was performed by comparing the test results with the histopathological and bacteriological results. The latter two tests yielded a prevalence of 4.16 %, a sensitivity of 71.43 %, and a specificity of 82.61 %. Based on these results, we concluded that CCT yielded satisfactory results and can be applied in diagnostic studies in buffaloes. The prevalence rate obtained using three distinct diagnostic methods suggests that Mycobacterium bovis was present in a few animals in the population evaluated.
Keywords: Buffalo; Mycobacterium bovis; Sensibility; Specificity; Zoonotic